Y-chromosomal haplotype diversity for 27 STR loci in the Tigray population (Northern Ethiopia). Issue 1 (December 2019) - Haddish, K.; Kumar, H.R.S.; Raddi, S.; Chierto, E.; Di Vella, G.; Bogale, A.L.; Kidane, E.; Yizengaw, A.; Getaneh, Y.; Robino, C.
Abstract: The Horn of Africa is among the main areas of origin of migrants trying to reach Europe through the so-called central Mediterranean route (from Libya to Sicily). Migration-related accidents in the Straits of Sicily are commonplace. In such circumstances, Y-STR analysis can effectively complement autosomal STR data in the identification of shipwreck victims and help reuniting families separated during the crossing. To expand currently available Y-STR haplotype reference data for Eastern Africa, the AmpF l STR YFiler Plus PCR Amplification kit (Thermo Fisher Scientific) was used to analyze samples from 247 Ethiopian Tigray volunteer donors. The Tigray ethno-linguistic group represents over 95% of the population in the Regional state of Tigray (Northern Ethiopia), and accounts for ∼50% of the population in neighboring Eritrea. The results obtained were compared with those available for other Eastern African ethno-linguistic groups and neighbor populations from Northern Africa and the Middle East.